Numerical analysis of molten metal shape in cold crucibles by 3D FEM - Cho, YW; Oh, YJ; Yi, KW; Chung, SH; Shim, JD (IOP PUBLISHING LTD, 1996)
A three-dimensional finite-element method with the edge finite element and the H-phi formulation technique has been adopted to analyze the electromagnetic field distribution in cold crucibles of different designs. The calculated magnetic flux density distribution and the meniscus shape of the molten metal agreed well with the measured values. The influences of the slit width, segment number of the cold crucible, frequency and position of the induction coil on the magnetic flux density distribution in a continuous casting type cold crucible have been calculated. The effects of density and electrical conductivity of liquid metals as well as the frequency of the induction coil on the meniscus shape of the melts have also been studied. Using the information obtained from the results of the calculation, four different designs of bottom support type cold crucibles were compared and an optimum design of cold crucible for melting reactive metals has been proposed.